Perinatal fluoxetine prevents the effect of pre-gestational maternal stress on 5-HT in the PFC, but maternal stress has enduring effects on mPFC synaptic structure in offspring - Gemmel, M.; Kokras, N; Dalla, C; Pawluski, J. L. (Neuropharmacology, 2018)
Maternal affective disorders are frequently treated with selective serotonin reuptake inhibitor medications (SSRIs); with up to 10% of women being prescribed these medications during pregnancy. Infant development depends on the early serotonergic environment, which is altered by perinatal SSRIs, raising concern about how these medications affect neural outcomes. While clinical and preclinical research suggests an impact of SSRIs on the developing brain, more research is needed to determine the effects on neuroplasticity, the serotonergic system, and the hypothalamic-pituitary-adrenal axis in neural regions mediating behavior. The current work investigated the effects of the SSRI, fluoxetine, on the serotonergic system in the prefrontal cortex (PFC) during pre-adolescence, and changes to synaptic markers and glucocorticoid receptor density in the cingulate cortex (medial PFC) of pre-adolescent and adult Sprague-Dawley male and female rats. To model aspects of Perinatal Depression and maternal anxiety, pre-gestational maternal stress was used resulting in male and female offspring from 4 groups: 1) control, 2) perinatal fluoxetine exposed, 3) pre-gestational maternal stress exposed, and 4) pre-gestational maternal stress + fluoxetine. Perinatal fluoxetine prevented the effects of maternal stress on 5-HT levels and 5-HT turnover ratio in the PFC of pre-adolescent offspring, particularly in females. However, pre-gestational stress reduced synaptophysin and PSD-95 densities in the cingulate cortex, effects that were more pronounced in males. Interestingly, perinatal fluoxetine exposure reduced GR density in adult males in this same brain area. Together, results show differential effects of perinatal SSRIs and pre-gestational maternal stress on neurodevelopment in the PFC of males and females.
Keywords: Age Factors; Animals; Animals, Newborn; Disks Large Homolog 4 Protein/metabolism; Drug Administration Schedule; Female; Fluoxetine/*administration & dosage; Gestational Age; Glucocorticoid receptor; HPA axis; Male; Neuroplasticity; Prefrontal Cortex/*metabolism; Pregnancy; Prenatal Exposure Delayed Effects/*pathology/*prevention & control; Psd-95; Rats; Rats, Sprague-Dawley; Selective Serotonin Reuptake Inhibitors/*administration & dosage; Serotonin/*metabolism; Sex differences; Sex Factors; Stress, Psychological/*complications; Synaptophysin; Synaptophysin/metabolism